Innovative Approach to Business Development in the Field of Waste in the Republic of Kazakhstan - Ausharipova, D.E.; Kulumbetova, L.B.; Tankova, E. (Karagandy University of the name of acad. E.A. Buketov, 2022)
Object: To research business development opportunities based on the principles and models of the closed-cycle economy in the field of solid household waste (SHW). Methods: General scientific methods (analysis and synthesis, comparison and analogy, hypothetical method) and special methods (formal-logical method, statistical analysis). Results: An analysis of the formation and processing of solid waste in the country revealed problems in this area. A comparative analysis of solid waste processing in Kazakhstan and non-CIS countries, as well as the profitability of waste recycling business in developed countries, showed that the waste sector is a prospective niche for the development of “green” business. The foreign studies contribute to the relevance of the use of business models of the circular economy, which implies the processing of waste into secondary raw materials and its use at different stages of the production process. The research identified the obstacles hindering the development of innovative businesses in the field of waste; suggested ways to solve the problems of the MSW sphere. Conclusions: The results depict that there is a significant potential for the development of an innovative business for the processing and recycling of waste in the field of solid waste management in Kazakhstan. To further develop this area, it is recommended to use the principles and business models of the circular economy, to create favorable conditions for entrepreneurial activity.
Қазақстан Республикасының қатты тұрмыстық қалдықтар саласындағы бизнесті дамытудың инновациялық тəсілі
Инновационный подход к развитию бизнеса в сфере твердых бытовых отходов Республики Казахстан
Keywords: green economy; circular economy; closed-cycle economy; business models; solid household waste (SHW); recycling; extended producer responsibility; recycling; innovative business; “green” business